2007
DOI: 10.4141/p05-086
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of herbicide resistance in two germplasm lines of Clearfield* rice (Oryza sativa L.)

Abstract: Wenefrida, I., Utomo, H. S., Meche, M. M. and Nash, J. L. 2007. Inheritance of herbicide resistance in two germplasm lines of Clearfield* rice (Oryza sativa L.). Can. J. Plant Sci. 87: 659-669. Inheritance of imidazolinone resistance in two germplasms of Clearfield rice lines, 93AS3510 and PWC-16, was studied using parents, F 1 hybrids, F 2 populations, and F 2:3 families. Germination tests were conducted in Petri dishes under controlled environments to reveal any discrete phenotypic responses to herbicide tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…All the plants that survived imazethapyr applications were confirmed as outcrosses by genetic analysis (Figure 2). The imazethapyr-resistant gene in CL161 rice is governed by a single incompletely dominant nuclear gene (Shivrain et al 2006;Wenefrida et al 2007). For CL161 rice the allele size was 130 and 135 base pairs (bp) with primers RM253 and RM234, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All the plants that survived imazethapyr applications were confirmed as outcrosses by genetic analysis (Figure 2). The imazethapyr-resistant gene in CL161 rice is governed by a single incompletely dominant nuclear gene (Shivrain et al 2006;Wenefrida et al 2007). For CL161 rice the allele size was 130 and 135 base pairs (bp) with primers RM253 and RM234, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Tolerance to imazamox, in terms of resistance index, among these varieties, varied between 1.2 and 4.2 (Table ). A study conducted on the germplasm of two IMI‐tolerant rice lines in the USA has established that the PWC‐16 line (derived from mutagenesis with EMS of USA rice variety Cypress) is 4.9‐fold more tolerant than the 93AS3510 line (Wenefrida et al ., ). A change to the size of the amino acid side‐chain may be the cause of insufficient herbicide binding, which may affect resistance level (Lee et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that this differential susceptibility results from a combination of the parent lines used to develop the new variety and the type of amino acid substitution. For example, serine‐asparagine substitution in the AHAS gene in rice line PWC‐16 has determined more herbicide‐tolerant rice than has glycine for glutamic acid substitution in this same gene in rice line 93AS3510 (Wenefrida et al ., ). In fact, this line was the progenitor of the first IMI‐tolerant rice variety in Brazil, and the glycine for glutamic acid substitution in the line was also found in weedy rice populations that escaped herbicide control with imazethapyr + imazapic in Brazilian rice fields (Roso et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Petri dish seed bioassay provides a reliable and simple method to evaluate IMI resistance in weed populations [ 35 ]. Results from the seed bioassay in the present study indicated that continuous exposure of pre-germinated seeds to IMI herbicides can significantly affect seed growth.…”
Section: Discussionmentioning
confidence: 99%